"The possibility to be creative is the reason I want to teach": Pre-service teachers' perceptions of creative teaching and philosophical education. Issue 1 (2021) - Levanon, Maya
Abstract: Contemporary studies suggest that creative teaching is important for young students' overall learning and development, yet the concept and its implications are still ambiguous for many educational practitioners. In this qualitative phenomenological study, I address this ambiguity by examining pre-service teachers' perceptions of the concept: I examine how participants with a shared experience perceive creativity and creative teaching, through the lens of their interpretation of their own teaching. After reviewing everyday creativity as our working concept, I explore participants' oral and written accounts as gathered through interviews and questionnaires. Based on the findings, which indicate a change over time in the way pre-service teachers perceive and understand creativity and creative teaching, I conclude that implementing philosophical practices such as: conceptual analyses, dialogues, and in-action reflection throughout their training and practicum years, is beneficial for the advancement of pre-service teachers creative teaching, and perhaps overall well-being. Highlights: Creativity is a unique human quality. Creativity facilitates full human development. All humans are creative. Education must facilitate creativity. Creativity is related to curiosity. Philosophical teachers' education facilitates teachers' creativity.